Transactions on Engineering Technologies International MultiConference of Engineers and Computer Scientists 2014 - Yang, Gi-Chul; Ao, Sio-Iong; Huang, Xu; Castillo, Oscar (Springer Netherlands : Imprint: Springer, 2015)
This volume contains revised and extended research articles written by prominent researchers who participated in the international conference on Advances in Engineering Technologies, which was held in Hong Kong, 12-14 March, 2014. Topics covered include engineering physics, engineering mathematics, scientific computing, control theory,  artificial intelligence, electrical engineering, communications systems, and industrial applications. The book offers the state of art of tremendous advances in engineering technologies and physical science and applications, and also serves as an excellent reference work for researchers and graduate students working with/on engineering technologies and physical science and applications.